Plant‐Based Substrate Materials for Flexible Green Electronics. Issue 12 (22nd June 2022) - Hwang, Youngkyu; Kim, Min Ku; Zhao, Ze; Kim, Bongjoong; Chang, Taehoo; Fan, Teng Fei; Ibrahim, Mohammed Shahrudin; Suresh, Subra; Lee, Chi Hwan; Cho, Nam‐Joon
Abstract: With the increasing use of soft and flexible electronics, there is a growing need to develop substrate materials that mitigate potential environmental risks associated with non‐degradable electronics waste from synthetic substrate materials. To address this issue, the authors develop a novel, 2D plant‐based substrate termed "sporosubstrate", which is made of non‐allergenic natural pollen. The pollen particle has a double‐layered architecture with an ultra‐tough sporopollenin exine, and a soft cellulose intine is engineered through an eco‐friendly process. In this manner, a readily available, economical, biodegradable, and biocompatible microgel can be prepared. This microgel can be used to create a variety of flexible shapes with customized mechanical, geometrical, electronic, and functional properties and performance characteristics such as thermal, chemical, and mechanical stability and optical transparency. Moreover, the authors demonstrate here different applications of the flexible natural substrate made of pollen microgel for use in electronic devices for health monitoring and wearable wireless heating. The results of this work point to opportunities for the development of a new class of flexible green electronics based on plant‐based materials in applications such as wearable sensors, implantable devices, and soft robotics. Abstract : The sporosubstrate as a novel biopolymer, which consists of nonallergenic natural pollen particles that are abundant, biocompatible, and ecofriendly shows high physical, chemical, and thermal stability. The sporosubstrate provides the opportunities to develop a new class of flexible green electronics based on plant‐based materials in medical applications such as wearable sensors and implantable devices.